Synthesis and Antifungal Activity of Azetidinone and Thiazolidinones Derivatives of 2-Amino-6-(2-naphthalenyl)thiazolo[3,2-d]thiadiazole - K. H. Patel; A. G. Mehta (E-Journal of Chemistry)
2-Amino-6-(2-naphthalenyl)thiazolo[3,2-d]thiadiazole [1] was prepared by treatment of KCNS and Br2 on 2-Amino-4-(2-naphthalenyl) thiazole. This amine on facile condensation with aromatic aldehydes afford Schiff Base/anils/azomethines(2a-h). These anils on cyclocondensation reaction with chloro acetyl chloride and thio glycolic acid (i.e. mercapto acetic acid) afford 2-azetidinones and 4-thiazolidinones respectively. The prepared compounds have been screened on some stains of fungai.